Réponses

  • Utilisateur Brainly
2014-03-10T22:19:07+01:00
Bonjour, 

Développer et réduire : 

A = ( x - 1 )( x + 9 ) + x²
A= x² + 9x - x - 9 + x²
A= 2x² + 8x - 9

B = 3x² + ( x - 1 )( 5 - x )
B= 3x² + 5x - x² - 5 + x
B= 2x² + 6x - 5

C = x ( x - 1 ) - 4 ( x + 1 )
C= x² - x - 4x - 4
C= x² - 5x - 4

D = ( x + 1 ) ( - x - 6 ) + 3x² - 2
D= - x² - 6x - x - 6 + 3x² - 2
D= 2x² - 7x - 8

Bonne soirée! :)
2014-03-10T22:20:33+01:00
Salut :)

Développer et réduire:

A = (x - 1)(x + 9) + x²
A = (x) x (x) + (x) x 9 - 1 x (x) - 1 x 9 + x²
A = x² + 9x - x - 9 + x²
A = 2x² + 8x - 9

B = 3x² + (x - 1)(5 - x)
B = 3x² + (x) x 5 + (x) x (-x) - 1 x 5 - 1 x (-x)
B = 3x² + 5x - x² - 5 + x
B = 2x²  + 6x - 5

C = x(x - 1) - 4(x + 1)
C = (x) x (x) + (x) x (-1) - 4 x (x) - 4 x 1
C = x² - x - 4x - 4
C = x² - 5x - 4

D = (x + 1)(-x - 6) + 3x² - 2

D = (x) x (-x) + (x) x (-6) + 1 x (-x) + 1 x (-6) + 3x² - 2
D = -x² - 6x - x - 6 + 3x² - 2
D = 2x² - 7x - 8

J'espère t'avoir aidé(e)! :)